A farmland-microclimate monitoring system based on the internet of things. (12th February 2020) - Yan, Maoling; Liu, Pingzeng; Tong, Cezhong; Wang, Xiujuan; Wen, Fujiang; Song, Changqing; Higgs, Russell; O'Hare, Gregory M.P.
Farmland's microclimate is a vital environmental factor that affects crop growth and yield formation. Based on clear perception, reliable transmission and intelligent processing of IoT concepts, a monitoring system of farmland microclimate is developed. The monitoring system consists of three layers. The perception layer integrates meteorological, soil, hydrological and other sensors to form a ground to air sensor cluster. The transport layer utilises the GPRS technology which covers the entire country for long distance and effectively transfers the collected data to the server in real time. The application layer is developed for receiving PC software and data storage. After three years of system operation, we have done statistical analysis on the length of life, the loss of data and the reliability of data. Results reveal that the system could ensure more than 80% of data integrity, and it can also secure good stability and reliability of the data.